Villages And Coronavirus Disease (A Study on The Policies Taken by The Government of Tainsala Village in Handling And Preventing COVID-19) - Nikolaus Uskono; Hendrikus Hironimus Botha; Wilfridus Taus (Jurnal Ilmiah Ilmu Administrasi Publik, 2022)
This paper aims at finding out what policies are implemented by the government of Tainsala Village in handling and preventing COVID-19. In this study, the researchers applied the qualitative method with a descriptive analysis approach based on the facts found in the field. Furthermore, concerning the employed data analysis technique, the researchers used three main components proposed by Miles & Haberman: data reduction, data presentation, and conclusions. Results showed that the government of Tainsala Village in handling and preventing COVID-19 have implemented several policies in the form of programs/activities, namely making COVID-19 posts at the entrance and exit of the village, providing quarantine locations, procuring and distributing face masks, hand sanitizer, & hand soap, and collaborating with the Health Office of North Central Timor Regency to disseminate information about COVID-19. The policies implemented have taken into account the participation aspects of the various existing stakeholders. Another finding is the use of local wisdom to accelerate herd immunity among the people of Tainsala Village.